Concerning Climate Change: Assessing the Potential of Islamic Business Entities to Promote Environmental Sustainability - Lucky Nugroho; Shinta Melzatia; Nurhasanah; Erik Nugraha; Audita Setiawan; Ibrahim Musa Gani (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
The current climate change has threatened human life, which has a negative impact on human health and the preservation of the natural environment. Therefore, this research aims to determine whether the existence of Islamic business entities can maintain environmental sustainability. The method used in this conceptual paper is a descriptive qualitative method that aims to answer the formulation of the problem: whether the concept of Islamic business entities can support environmental sustainability. The results of this conceptual paper are: (i) Islamic business entities have a strong commitment to environmental sustainability; (ii) The pillars of Islamic business entities include financial aspects, social aspects, environmental sustainability aspects, and spiritual aspects; (iii) The primary purpose of the existence of Islamic business entities is to provide safety in the world and happiness in the hereafter; and (iv) Islamic business entities aim to provide sustainable benefits to society and the environment. The implication of this conceptual paper is to provide scientific knowledge in environmental sustainability and Islamic economics.